2011
DOI: 10.1080/01434632.2010.541917
|View full text |Cite
|
Sign up to set email alerts
|

The value of adopting multiple approaches and methodologies in the investigation of Ethnolinguistic Vitality

Abstract: The concept of 'Ethnolinguistic Vitality' (EV) has received variable acceptance and support since its introduction by Giles, Bourhis, and Taylor. It has especially proven to be a valuable heuristic in studies of language maintenance and shift. However, the reliability and validity of the instruments used to investigate EV, especially questionnaires used to test subjective vitality, have proven to be more problematic. This position paper introduces some of the issues that have been considered as difficult in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…From the early days of exploration into ethnolinguistic vitality, language use has been further hypothesized as a strong determinant in the perceiving of identity. Gao, Schmidt, andGudykunst (1994), andMcEntee-Atalianis (2011) found that ethnic identity has influenced ethnolinguistic vitality. In other words, those who have a strong ethnic identity have high ethnolinguistic vitality.…”
Section: Vitality Language Use and Identitymentioning
confidence: 99%
“…From the early days of exploration into ethnolinguistic vitality, language use has been further hypothesized as a strong determinant in the perceiving of identity. Gao, Schmidt, andGudykunst (1994), andMcEntee-Atalianis (2011) found that ethnic identity has influenced ethnolinguistic vitality. In other words, those who have a strong ethnic identity have high ethnolinguistic vitality.…”
Section: Vitality Language Use and Identitymentioning
confidence: 99%
“…Methodologically, the theory has been criticised for its main reliance on quantitative methods such as questionnaires to measure the vitality of the group (see Ehala & Zabrodskaja, 2011;Lewis, 2000;McEntee-Atalianis, 2011). It is suggested that EV can be effectively measured using quantitative and qualitative methods such as ethnographic approaches.…”
Section: Ethnolinguistic Vitalitymentioning
confidence: 99%
“…Methodologically, perceptions of vitality are complex and not adequately addressed quantitatively only. Qualitative methods or a combination of quantitative and qualitative methods can better capture the complexity of vitality perceptions (Hatoss, 2013;Lewis, 2000;McEntee-Atalianis, 2011). Theoretically, SEVQ has been criticised for measuring the outgroups vitality in respect to strength, power and status perceptions only, ignoring that there might be other factors affecting vitality such as motivation (Karan, 2011), ethnolinguistic identification (Hogg and Rigoli, 1996) or intergroup distance (Ehala, 2010;Ehala & Zabrodskaja, 2011).…”
Section: Subjective Ethnolinguistic Vitalitymentioning
confidence: 99%
“…Reasonably objective indices of these aspects of ELV can be obtained through archival and ethnographic work (e.g., censuses, media analyses, policy reviews, etc. ; see Kindell and Lewis and McEntee‐Atalianis , for in‐depth discussions of ELV assessment).…”
Section: Subjective Ethnolinguistic Vitalitymentioning
confidence: 99%